Draft Annual Plan 1979-80 Union Territory of Delhi - Planning Commission (Planning Commission, 1978)
Major Heads of Development Outlays and Expenditure Sector/Agency wise Proposed Outlay Minor heads-Outlays and Expenditure Schemes Outlay and Expenditure Agriculture and Allied Services Cooperation Water and Power Development, Industry Transport and Communication Social and Community Services
Planning Department
Planning Department